Assessing human B cell repertoire diversity and convergence. Issue 1 (26th June 2018) - Imkeller, Katharina; Wardemann, Hedda
Summary: A hallmark of the adaptive immune system is the specificity of B cell and T cell responses. Mechanistically, this feature relies on the fact that the two genes that encode B cell and T cell antigen receptors are not germline encoded and instead are assembled from a large number of small gene segments during lymphocyte development. The underlying somatic gene recombination process can generate a quasi‐unlimited repertoire of antigen receptors. The high degree of diversity is essential to guarantee recognition of nearly any antigenic structure to protect from the large variety of potential invading pathogens and to keep the balance with commensals. Due to the enormous complexity of the antigen receptor repertoire, our understanding of its actual size and functional convergence at the level of the individual and the population is still limited. A better understanding of the actual degree of diversity could help to predict adaptive immune responses and would have wide implications for the development of preventive and therapeutic measures against infectious and autoimmune diseases as well as cancer. Here, we discuss the recent advances in the field with a specific focus on B cells and the function of antibodies.